Long‐term outcomes of rotational atherectomy for the percutaneous treatment of chronic total occlusions. Issue 5 (28th December 2016) - Azzalini, Lorenzo; Dautov, Rustem; Ojeda, Soledad; Serra, Antonio; Benincasa, Susanna; Bellini, Barbara; Giannini, Francesco; Chavarría, Jorge; Gheorghe, Livia L.; Pan, Manuel; Carlino, Mauro; Colombo, Antonio; et al.
Abstract : Objectives . To study the long‐term outcomes of rotational atherectomy (RA) for chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Background . There is little evidence on the incidence, procedural results and long‐term outcomes of RA for CTO PCI. Methods . This registry included data from consecutive patients undergoing CTO PCI at four specialized centers. Major adverse cardiac events (MACE: cardiac death, target‐vessel myocardial infarction and ischemia‐driven target‐vessel revascularization) on follow‐up were the primary endpoint. Results . A total of 1003 patients were included. Of these, 35 (3.5%) required RA. As compared with Conventional PCI, RA patients were older (68.9 ± 9.5 vs. 64.6 ± 10.7 years, P = 0.02), had higher prevalence of diabetes (58% vs. 37%, P = 0.01) and of a J‐CTO score ≥2 (80% vs. 58%, P = 0.009), driven by severe calcification. Antegrade wire escalation was used more frequently in RA (74% vs. 53%, P = 0.08). RA was performed for balloon failure‐to‐cross in 51% and failure‐to‐expand in 49%. One burr was utilized in 86%. The 1.25‐mm burr was the largest burr used in 43%. Slow flow/no‐reflow was observed in 17%. No other serious RA‐related complications were observed. Procedural success was 77% vs. 89% ( P = 0.04) in RA vs. Conventional PCI. After a mean follow‐up of 658 ± 412 days, MACE rates were similar between groups (15% vs. 13%, P = 0.70). Conclusions . The use of RA in CTO PCI was safe, despite a worse patient risk profile and higher procedural complexity, as compared with conventional techniques. Although procedural success was lower in the RA group, there were no differences in long‐term clinical outcomes between groups. © 2016 Wiley Periodicals, Inc.